2017
DOI: 10.3892/ol.2017.6494
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibitor enhances sensitivity to chemotherapeutic drugs in multidrug resistant hepatocellular carcinoma cells

Abstract: Abstract. The aim of the present study was to investigate the association between the mitogen-activated protein kinase (MAPK) signal transduction pathway and multidrug resistance in hepatocellular carcinoma cells. A Cell Counting Kit-8 assay was used to determine the drug sensitivity of HepG2 and HepG2/ADM hepatocellular carcinoma cell lines in combination with the MAPK/extracellular-signal-regulated kinase kinase (MEK) inhibitor U0126. Flow cytometry was used to analyze the rate of apoptosis. The reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The study by Fang et al (28) reported that downregulation of UBC9 increased the sensitivity of HCC cells to doxorubicin. In addition, Meng et al (29) indicated that MEK inhibitors enhance the sensitivity of multidrug resistant HCC cells to chemotherapeutic drugs. Previous studies further reported that norcantharidin suppresses proliferation, inhibits invasion and metastasis, and induces apoptosis in HCC cells, which is a potential treatment of HCC (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Fang et al (28) reported that downregulation of UBC9 increased the sensitivity of HCC cells to doxorubicin. In addition, Meng et al (29) indicated that MEK inhibitors enhance the sensitivity of multidrug resistant HCC cells to chemotherapeutic drugs. Previous studies further reported that norcantharidin suppresses proliferation, inhibits invasion and metastasis, and induces apoptosis in HCC cells, which is a potential treatment of HCC (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, chemoresistance remains a major barrier for chemotherapeutic agents, prompting considerable research on suitable treatments for HCC (Asghar & Meyer, ). MAPKs play an important role in regulating growth, metastasis, apoptosis, and chemoresistance (Meng et al, ). Previous research has shown that U0126, a highly selective inhibitor of both MEK1 and MEK2 (types of MAPK/Erk kinases), can enhance sensitivity to chemotherapeutic drugs in the HepG2/ADM cell model of multidrug resistance (Meng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MAPKs play an important role in regulating growth, metastasis, apoptosis, and chemoresistance (Meng et al, 2017). Previous research has shown that U0126, a highly selective inhibitor of both MEK1 and MEK2 (types of MAPK/Erk kinases), can enhance sensitivity to chemotherapeutic drugs in the HepG2/ADM cell model of multidrug resistance (Meng et al, 2017). Accordingly, to better understand the causes of chemoresistance, this study focused on the effects of exposure to nontoxic concentrations of AlCl 3 on 5-FU chemoresistance in HCC (HepG2) cells and attempted to elucidate the underlying mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6) ABCB1 is a target of the Ras/Raf signaling pathway, suppression of p38, ERK or JNK pathways enhanced sensitivity to chemotherapeutic drugs in multidrug resistant tumor cells. [7][8][9][10] Paris polyphylla var. yunnanensis (Franch.)…”
Section: Introductionmentioning
confidence: 99%